SETTLEMENT OF CRIMINAL MATTERS THROUGH MALAY CUSTOMARY INSTITUTIONS WITH THE CONCEPT OF RESTORATIVE JUSTICE IN LIPAT KAIN KAMPAR KIRI OF KAMPAR REGENCY - Elmayanti, Elmayanti; Deliana, Evi; Rasudin, Nurahim (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
Customary law is religiously functional law, so that customary law fulfills a social function or social justice. Thus, the community and its members carry out these normative orders without seeing them as coercion, but because they assume they are as such. The aim of the law is justice, expediency and legal certainty, and these three elements constitute an inseparable unity. Justice is the moral foundation of the law and, at the same time, the benchmark for a positive legal system. In other words, justice has always been the basis of the law. Without justice, a rule can not be called a law. The highest possible justice to be achieved in the mediation of sanctions is the agreement of the parties involved in the criminal case.